Minimisation of AC Grid Side Input Power Factor Angle for Three-phase AC to Three-phase AC Matrix Converter under Varying Load - Basak Abhinandan; Syam Prasid; Mukherjee Kaushik (Power Electronics and Drives)
Minimisation of AC grid side input power factor angle for a ‘matrix converter (MC)’ improves the efficiency of the grid. Input volt-ampere requirement is minimum if the current drawn by the ‘MC’ is sinusoidal and input displacement power factor (IDPF) is unity. A MC is inherently capable of maintaining a unity displacement power factor (UDPF) angle at its input terminals. However, the input currents drawn from the grid are not sinusoidal. The high-frequency ripples are suppressed by input current filters (ICFs).These filters additionally introduce a leading phase angle for the current which varies with the loading. This phase lead can be compensated by adjusting the angle between the input current space vector and the input voltage space vector of the MC. The computation of this adjustment angle depends on the estimation of power losses in the switching devices. A simple method is proposed in this paper to estimate the switching losses without measuring device voltages and currents using the perturbation technique. The perturbation logic depends on input current, instantaneous active and reactive power computed at regular intervals of time. The proposed method effectively minimises the IDPF angle very close to zero. The experimental results are included for validation,